A magyar vállalatok terjeszkedése a volt jugoszláv államokban - Juhász, Krisztina (Közép-Európai Közlemények, 2011)
After 2000 Hungary is playing an active role in the process of international direct investments. During the last years, Hungarian firms has began investing abroad, and became regional multinational companies (such as OTP and MOL). The FDI outward stock of Hungary reaches more than 11 milliard Euros, what means that Hungary is the second largest investor of the region. At least half of that investments are „virtual indirect OFDI”. The primary host region of Hungarian investments is the Central and Eastern Europe, mainly the surrounding countries. In the ex-Yugoslavian countries, Hungarian investors play a relative important role: in Montenegro Hungary is the first, in Macedonia the 3rd and in Croatia the 4th biggest investor. The main reason of the Hungarian expansion is to gain access to new markets and to use some firm-specific advantages, mainly the know how, the experiences in the privatisation and the connection capital of the management. For the small companies, the high share of Hungarian nationalities in some regions is an important factor for cross-boarder investments. The use of the country-specific advantages of the host countries (such as cost factors) can lead to a higher competitiveness of the home country as well.